Inhibitory Effect of a Combined Treatment of Glycyrrhizin and Caffeine on Tumor Promotion by 12-O-Tetradecanoylphorbol-13-Acetate in Two-Stage Carcinogenesis in Mouse Skin - Ken Yasukawa (Journal of Pharmacy and Nutrition Sciences, 2013)
Cancer prevention is an important problem in the field of public health. Glycyrrhizin, a natural sweetening agent, is one of the components of licorice and caffeine in coffee and tea. Glycyrrhizin and caffeine were found to inhibit tumor promotion by 12-O-tetradecanoylphorbol-13-acetate (TPA) in two-stage carcinogenesis in mouse skin. Furthermore, the combined treatment of glycyrrhizin and caffeine is more effective than their single treatment on tumor promotion by TPA in mice following initiation with 7,12-dimethylbenz[a]anthracene.